Identification of oil palm species using electrophoresis. - Gan, Yik Yuen; Abd. Rahman, Ahmad; Tan, S. G.; Abdol, Idris (1983)
Analysis of samples of young leaves from mature palms revealed that, of the six enzymes assayed, esterase and acid phosphatase were the most useful genetic markers for distinguishing between (1) the pisifera, tenera and dura forms of Elaeis guineensis, (2) E. guineensis and E. [Corozo] oleifera and (3) E. guineensis X E. oleifera F1 hybrids and their parents. Certain bands of the two enzymes were species specific and hybrid bands only occurred in the hybrids.